Comparison of 18F-NaF Imaging, 99mTc-MDP Scintigraphy, and 18F-FDG for Detecting Bone Metastases - Dadgar, Habibollah; Norouzbeigi, Nasim; Jokar, Narges; Zareizadeh, Jafar; Gholamrezanezhad, Ali; Ahmadzadehfar, Hojjat; Abbaszadeh, Moloud; Assadi, Majid (World Journal of Nuclear Medicine, 2022)
Bone is a common metastasis site in several malignancies, most importantly prostate and breast cancers. Given the significance of the early and accurate diagnosis of bone metastases for preliminary staging, treatment planning and monitoring, restaging, and survival prediction in patients with malignancy, it is critical to compare and contrast the strengths and weaknesses of imaging modalities. Although technetium-99m-labeled diphosphonates [99mTc-MDP] scintigraphy has been used for assessing skeletal involvement, there is a renewed interest in fluorine-18-labeled sodium fluoride [18F-NaF] bone imaging with positron emission tomography or positron emission tomography/computed tomography, since this approach provides essential advantages in bone metastases evaluation. This review study aimed to discuss the basic and technical aspects of 18F-NaF imaging and its mechanism of action, and compare this modality with the 99mTc-MDP bone scan and 18F-fluorodeoxyglucose using current evidence from the pertinent literature and case examples of the center in the study.
Keywords: skeletal metastases; fluorodeoxyglucose (FDG); sodium fluoride (NaF); 99mTc-MDP